Mucosal and cellular immune responses elicited by nasal and intramuscular inoculation with ASFV candidate immunogens - Xu, Lulu; Hao, Fei; Jeong, Dae Gwin; Chen, Rong; Gan, Yuan; Zhang, Lei; Yeom, Minjoo; Lim, Jong-Woo; Yu, Yanfei; Bai, Yun; Zeng, Zhiyong; Liu, Yongjie; et al. (Frontiers in Immunology, 2023)
African swine fever (ASF) is an infectious disease caused by African swine fever virus (ASFV) that is highly contagious and has an extremely high mortality rate (infected by virulent strains) among domestic and wild pigs, causing huge economic losses to the pig industry globally. In this study, SDS‒PAGE gel bands hybridized with ASFV whole virus protein combined with ASFV-convalescent and ASFV-positive pig serum were identified by mass spectrometry. Six antigens were detected by positive serum reaction bands, and eight antigens were detected in ASFV-convalescent serum. In combination with previous literature reports and proteins corresponding to MHC-II presenting peptides screened from ASFV-positive pig urine conducted in our lab, seven candidate antigens, including KP177R (p22), K78R (p10), CP204L (p30), E183L (p54), B602L (B602L), EP402R-N (CD2V-N) and F317L (F317L), were selected. Subunit-Group 1 was prepared by mixing above-mentioned seven ASFV recombinant proteins with MONTANIDETM1313 VG N mucosal adjuvant and immunizing pigs intranasally and intramuscularly. Subunit-Group 2 was prepared by mixing four ASFV recombinant proteins (p22, p54, CD2V-N1, B602L) with Montanide ISA 51 VG adjuvant and immunizing pigs by intramuscular injection. Anticoagulated whole blood, serum, and oral fluid were collected during immunization for flow cytometry, serum IgG as well as secretory sIgA antibody secretion, and cytokine expression testing to conduct a comprehensive immunogenicity assessment. Both immunogen groups can effectively stimulate the host to produce ideal humoral, mucosal, and cellular immune responses, providing a theoretical basis for subsequent functional studies, such as immunogens challenge protection and elucidation of the pathogenic mechanism of ASFV.